Discussion on "An effective method for the explicit solution of sequential problems on the real line" by Sören Christensen. Issue 1 (2nd January 2017) - Steland, Ansgar
ABSTRACT: The results of Christensen are remarkable and motivate some comments on large-sample approximations of the (discrete versions of the) stopping times related to the running maximum process.